The Role of Physical Culture and Sports in the Formation of a Healthy Lifestyle of a Student - Satimov A’zamjon Ikromovich; Murodov Nozimjon Olimjonovich; Ortiqov Umidjon Khudoiberdiyevich (Research Parks Publishers, 2021)
This article discusses the role of sports and physical education in shaping a healthy lifestyle for students. The factors necessary for a healthy lifestyle are analyzed and explained